The Naïve nurse: revisiting vulnerability for nursing - Tomm-Bonde Laura (BMC Nursing, 2012)
Abstract Background Nurses in the Western world have given considerable attention to the concept of vulnerability in recent decades. However, nurses have tended to view vulnerability from an individualistic perspective, and have rarely taken into account structural or collective dimensions of the concept. As the need grows for health workers to engage in the global health agenda, nurses must broaden earlier works on vulnerability, noting that conventional conceptualizations and practical applications on the notion of vulnerability warrant extension to include more collective conceptualizations thereby making a more complete understanding of vulnerability in nursing discourse. Discussion The purpose of this paper is to examine nursing contributions to the concept of vulnerability and consider how a broader perspective that includes socio-political dimensions may assist nurses to reach beyond the immediate milieu of the patient into the dominant social, political, and economic structures that produce and sustain vulnerability. Summary By broadening nurse’s conceptualization of vulnerability, nurses can obtain the consciousness needed to move beyond a peripheral role of nursing that has been dominantly situated within institutional settings to contribute in the larger arena of social, economic, political and global affairs.